Eksistensi Radikalisme Jamaah Ansharut Daulah Kota Bima, Indonesia - Muhammad Husni; Tina Pulubuhu, Dewie Aries; Mengge, Buchari (Universitas Muhammadiyah Sorong, 2023)
This research aims to find out how radicalism develops and influences members of the JAD, Bima group and how the concept of amaliyah is implemented by group members using Berger and Luckmaan's social construction theory which is described through the process of internalization, objectivation, and externalization. This research is qualitative with a case study approach, semi-structured interviews were conducted with informants selected using a purposive sampling technique. The research shows that the JAD group becomes radicalized when there is an incomplete understanding of the teachings of Islam, they are taught a book that discusses the law of blood against those who oppose or fall into the group of infidels entitled Ahkamuddimah. The JAD group has the concept of iddat or war preparation which begins with the process of teaching Islamic values and is followed by training to strengthen mentally and physically. The concept of amaliyah is recognized as jihad or a struggle to defend religion in order to invent a state life based on Islam. The internalization process is interpreted as a value-teaching activity. At the same time, objectivation is a process where members strengthen their position as part of the group by learning religious values and training consistently. The externalization process is interpreted as the implementation of values and awareness of realizing religious teachings in real actions known as jihad through extreme actions. As a result of the JAD group, Bima contributed to shaping the negative public perception of Islam.